Design of an energy‐efficient and reliable data delivery mechanism for mobile ad hoc networks: a cross‐layer approach. (4th July 2014) - Hassan, Mohammad Mehedi; Kamruzzaman, S. M.; Alamri, Atif; Almogren, Ahmad; Alelaiwi, Abdulhameed; Alnuem, Mohammed; Islam, Md. Manowarul; Razzaque, Md. Abdur; Xiang, Yang; Pathan, Mukaddim; Wei, Guiyi; Fortino, Giancarlo
Summary In a mobile ad hoc network, the data packet may fail to be delivered for various reasons mostly for route failure, congestion, and battery energy drain. Hence, providing reliable and timely data delivery in this network in an energy‐efficient way is challenging. Although there exist several solutions to solve these problems, they can handle either route failure or congestion or energy‐efficient routing. Hence, to cope up with all the problems simultaneously, we propose a route failure and congestion‐aware energy‐efficient cross‐layer design that spans the transport and network layer. In the transport layer, we introduce the concept of local packet buffering during link failure and congestion. As a result, the packet dropping rate of the network and energy consumption decreases. In the network layer, a routing protocol is proposed for selecting the energy‐efficient path for data transmission. It uses the buffering mechanism in case of route maintenance. In addition, we employ a multilevel congestion detection and control mechanism at the source and intermediate nodes that can judiciously take the most appropriate decision for congestion control in the network proactively. The simulation results showed that the proposed cross‐layer design provided better performance as compared with the state‐of‐the‐art protocols. Copyright © 2014 John Wiley & Sons, Ltd.